2004
DOI: 10.1086/382195
|View full text |Cite
|
Sign up to set email alerts
|

Oculocutaneous Albinism Type 4 Is One of the Most Common Types of Albinism in Japan

Abstract: Oculocutaneous albinism (OCA) is a complex genetic disease with great clinical heterogeneity. Four different types of OCA have been reported to date (OCA1, OCA2, OCA3, and OCA4). MATP was recently reported in a single Turkish OCA patient as the fourth pathological gene, but no other patients with OCA4 have been reported. Here, we report the mutational profile of OCA4, determined by genetic analysis of the MATP gene in a large Japanese population with OCA. Of 75 unrelated patients that were screened, 18 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
156
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 11 publications
2
156
2
Order By: Relevance
“…30 OCA4 is one of the most common forms of albinism in the Japanese population. 31,32 Polymorphism within the SLC45A2 gene is a major determinant of normal variation in skin pigmentation, 33 with the rs16891982 b.1122G/C, p.374Leu/Phe change of the encoded protein, MATP, associated with the lighter pigmentation phenotypes of Europeans. 24 A heavier OCA pigmentation phenotype has been noted as being linked with darker familial background pigmentation, indicating that other genes may modify the OCA condition.…”
Section: Introductionmentioning
confidence: 99%
“…30 OCA4 is one of the most common forms of albinism in the Japanese population. 31,32 Polymorphism within the SLC45A2 gene is a major determinant of normal variation in skin pigmentation, 33 with the rs16891982 b.1122G/C, p.374Leu/Phe change of the encoded protein, MATP, associated with the lighter pigmentation phenotypes of Europeans. 24 A heavier OCA pigmentation phenotype has been noted as being linked with darker familial background pigmentation, indicating that other genes may modify the OCA condition.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in Slc45a2 have been identified in an increasing number of animal species [9,10,26,27,33,37], and the phenotype of Slc45a2 varies from hypopigmentation as severe as that seen in OCA1 to some pigmentation with brown hair and eyes [13]. The OCAO suncus described herein, having almost pure white coats, may serve as a unique disease model of human OCA4 and will provide some insights to the function of SLC45A2.…”
Section: Discussionmentioning
confidence: 80%
“…Homologous mutations affecting the aspartic acid in the fourth transmembrane domain, resulting in light beige and cream coat colors, have been reported in the mouse (uw dbr ) and horse, respectively [26,27,40]. Moreover, D157N, a missense mutation that lies in the second cytoplasmic loop close to the fourth transmembrane domain, is the most frequent mutation in Japanese OCA4 patients [13]. However, functional studies of these mutant SLC45A2s have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OCA3 is rare, with notable frequency only in African populations (3). The incidence of OCA4 is not known; however, it appears to be more prevalent in Japanese populations (7).…”
Section: Oculocutaneous Albinismmentioning
confidence: 99%